Determinantes del margen de Intermediación financiera para el periodo 2005-2017 (2018)
The purpose of this document is to expose inductively how the determinants of the intermediation margin (activity, tax and consumption variables) explain the evolution of the intermediation margin for the period between 2005 and 2017.